PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN PENGENDALIAN DIRI TERHADAP PERILAKU KONSUMTIF MAHASISWA PRODI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS PASIR PENGARAIAN - Irianti Asisi; Purwantoro (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of financial literacy, lifestyle and self-control both partially and simultaneously on the consumptive behavior of students of the Management Study Program at the Faculty of Economics, University of Pasir Pengaraian. The population is students of the Faculty of Economics, University of Pasir Pengaraian who are still actively studying in 2018. The research sample used a purposive sampling technique with a total of 90 people. The independent variables in this study are financial literacy (X1), lifestyle (X2), self-control (X3) and the dependent variable of consumptive behavior decisions (Y). Data collection methods using observation, questionnaires, documentation and interviews. Data analysis using multiple linear regression with the SPSS program. Partially, the financial literacy t-test was obtained 7.705, lifestyle 0.322 and self-control 8.413. Simultaneously, an F-count of 105,437 was obtained. The results showed that 77.9% of consumer behavior was influenced by financial literacy, lifestyle and self-control, while the remaining 22.6% was influenced by other variables not examined in this study. The conclusions of this study in the partial test (t test) are only variables of financial literacy and self-control that have a positive and significant effect on consumptive behavior, whereas in simultaneous testing (F test) financial literacy, lifestyle and control the effect simultaneously on consumptive behavior.